PERLINDUNGAN HUKUM TERHADAP KORBAN PENYALAHGUNAAN NARKOTIKA BERDASARKAN UNDANG-UNDANG NARKOTIKA DI LEMBAGA PEMASYARAKATAN KEROBOKAN - Kadek Wisnu Permana Putra; A.A Gde Putra Arjawa; Kadek Dedy Suryana (Yayasan Nusantara Hasana Berdikari, 2024)
The increase in narcotics crimes is caused by various factors, one of which is weak supervision of narcotics distribution, light sentences imposed by law, so that narcotics users and dealers do not feel deterred. Likewise, we often know that at the Kerobokan Penitentiary, where inmates, especially narcotics criminals, are serving sentences, where they can carry out narcotics transactions from behind bars, this shows how weak supervision is by the Kerobokan Penitentiary (LP). The formulation of the problem raised is 1. What is the policy formulation for psychotropic crime? 2. What is the legal protection for victims of psychotropic crime? This research uses a normative juridical approach, meaning that the approach to the relevant laws and regulations is contextualized with the reality on the ground. Sources of legal material for this research are literature from books and literature and the opinions of scholars related to the issues discussed. The formulation policy for psychotropic crimes in Law no. 35 of 2009 is the policy of the legislators in formulating the subjects of psychotropic crimes (which can be punished), namely in the form of individuals, corporations and special subjects, namely heads of hospitals, doctors, health centers, medical centers and heads of drug factories. As well as the policy of formulating acts which are declared as psychotropic criminal acts including acts which are declared as psychotropic criminal acts which include acts without the right to produce, own and distribute psychotropic substances in Law no. 35 of 2009, and legal protection for victims of psychotropic crimes is very necessary, apart from being subject to sanctions, rehabilitation and supervision are carried out, so that victims can be protected and return to the right path, not in conflict with norms, the state and religion.